Perempuan Penenun: Menelusuri Pengalaman Perempuan Penenun di Sumba dari Sudut Pandang Teologi Keindahan menurut John Navone - Irene Umbu Lolo (Asosiasi Teolog Indonesia, 2018)
Knowledge, capacity, and creativity are God’s gifts to women, and these gifts enable women to weave cloth. From a perspective of theological aesthetics, the activity of such weaving women may be seen as a form of participation in God’s beauty, just as their experience as women weavers become an experience of the beauty of God. These women express understanding, knowledge, and awareness of their own personhood, namely, as human beings who through the process and experience of weaving cannot be separated from one another, nature, or God. This article locates the experience of women weavers as an important site for theological aesthetics. Such experience invites more than mere recognition or appreciation, even as it might also function as a basis for a contextual theology in Sumba. This is so, because—as I explicate—such experience amounts to an experience of the beauty of God.